Analisis Pengamanan Jaringan Pada Protokol IPv6 Menggunakan Multi-Layer IPSec - Asrizal Asrizal; Syahril Efendi; Zakarias Situmorang (Program Studi Sistem Informasi, 2019)
Security is an important aspect in computer network operations. To support, computer network security, various security methods have been developed, both in application level security, such as Pretty Good Privacy (PGP), end-system level security, such as Socket Secure Layer (SSL), direct-link level security such as Multi Protocol Level Switching (MPLS) and IP layer security such as IP Security (IPSec). IPSec is a collection of protocols for securing networks through authentication and IP packet encryption. On the other hand, Internet Protocol Version 4 (IPv4) as a network protocol is not safe enough and is no longer able to serve the needs of new IP addresses around the world, and will soon be replaced with IPv6. Therefore, it is necessary to examine various security methods that can be developed in IPv6. In this study, the author will analyze the Multi-Layer IPSec in securing IPv6 networks.Keywords: IPv6, IPSec, Multi-Layer IPSec